SOCIAL ASPECTS OF ENVIRONMENTAL SAFETY (INNOVATIVE ECONOMY, 2020)
Dykan O.V., Mashchenko M.А. SOCIAL ASPECTS OF ENVIRONMENTAL SAFETYPurpose. The aim of the article is the determination of the social variant of environmental safety and analysis of the indicators of the overall mechanism for evaluating social threats in the prolonged study to ensure the environmental safety of the state.Methodology of research. The methods of analysis and synthesis, graphical and analytical method of research are used in the article for determining the indicators of the criterion assessment of social security, social component, an assessment of social threats.Findings. It is established that the formation of new social and economic relations in Ukraine on the basis of reforming the social and economic model requires an understanding of approaches and the development of the concept of national security, and within the framework of the general concept, the substantiation of the main provisions of Ukraine's environmental security.The importance of the social variant of environmental safety has been determined and the necessity of implementation of the complex results of social and ecological and economic research in the general state strategy for reforming the social and economic model and the further implementation of the Concept of Sustainable Development have been substantiated.It is proved that one of the most important approaches to achieve invariant safety is the introduction of a developed general mechanism for assessing social threats based on selected indicators and criterion assessments.Originality. It is substantiated that one of the most important approaches to achieve invariant safety is defined in the article and the author has developed a general mechanism for assessing social threats based on selected indicators and criterion assessments.Practical value. The obtained results of the research are aimed at supporting a sufficient standard of living of the population; provision of social and political security of society; maintaining the foundations of the constitutional system; formation of a stable system of national values and interests.Key words: environmental safety; social security; social and ecological economic approach; state.
Keywords: Key words; environmental safety; social security; social and ecological economic approach; state.